Advokasi Peningkatan Partisipasi Perempuan dalam Bidang Sosial Ekonomi - Ruland Willy Jack Sumampouw; Engkur; Antaiwan Bowo Pranogyo; Megayani; Junaidi Hendro (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2026)
Women in marginalized urban communities often face barriers to economic participation, including limited access to business capital, low financial and digital literacy, and the double burden of domestic and economic responsibilities. This community service program aimed to promote women’s participation in socio-economic activities through economic empowerment advocacy. The program was conducted using lectures and interactive discussions to identify challenges and explore potential solutions. The results showed increased participant awareness of the importance of women’s economic empowerment and highlighted key obstacles faced by marginalized women. The activity also produced recommendations for strengthening legal protection, expanding social security access, and increasing government support for women’s empowerment programs. These recommendations are expected to contribute to the development of more inclusive and gender-responsive policies.